Model Based Controller And Observer For Boost Converter - Siti Halma, Johari; Khairul Azha, A. Aziz; Suziana, Ahmad; Khalil Azha, Mohd Annuar; Mahidzal, Dahari (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
This paper describes an analysis of modern controller, which uses output voltage as feedback to regulate its output voltage to a desired value without steady-state oscillations with the aid of Matlab® & Simulink® simulation software. This methodology is proposed to develop modern controller for application on boost DC-DC converter system with no parasitic components in the circuit. It is implemented on the system by analyzing state-space modeling. By specifying switches’ ON and OFF position and solving node equations of the corresponding circuit topology, a set of state-space equations for each topological mode are recorded. Power simulator (PSIM) simulation results obtained are used to validate this approach. The minimum inductor value and minimum current flow on boost converter are calculated to ensure it operates in continuous current mode. In comparison to the open-loop controllers, the closed-loop controllers consist of a state feedback controller, optimal controller, state feedback with the feed forward controller and integral controller are performed in simulation. These modern controllers are simulated to analyze transient response and percentage of overshoot of boost converter output voltage. If the output of the system is observable, a full state observer can also be implemented. All collected results are compared to find the best controller, which produces a minimum error.